2015
DOI: 10.5830/cvja-2015-018
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, attitude and behaviour regarding dietary salt intake among medical students in Angola: cardiovascular topic

Abstract: SummaryBackgroundLevels of salt consumption and its awareness among medical students in Angola remain insufficiently studied. This study determined salt intake and assessed medical students’ knowledge, attitude and behaviour regarding salt consumption.MethodsWere collected 24-hour urine samples from a random sample of 123 undergraduate medical students aged 17–43 years who were studying at the University of Agostinho Neto in Luanda. Their knowledge, attitude and behaviour regarding dietary salt were surveyed. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
21
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 25 publications
4
21
2
Order By: Relevance
“…Sajwani et al [20] found that higher knowledge levels in Pakistani medical students were not reflected in their dietary practices. A study in Angola reported that although medical students were aware of the health consequences of a high salt intake, few looked at sodium levels on food labels before consuming products [26]. Another survey indicated that UK healthcare students were well informed about health related consequences of a high salt intake but had not reduced their own consumption of salt [27].…”
Section: Discussionmentioning
confidence: 99%
“…Sajwani et al [20] found that higher knowledge levels in Pakistani medical students were not reflected in their dietary practices. A study in Angola reported that although medical students were aware of the health consequences of a high salt intake, few looked at sodium levels on food labels before consuming products [26]. Another survey indicated that UK healthcare students were well informed about health related consequences of a high salt intake but had not reduced their own consumption of salt [27].…”
Section: Discussionmentioning
confidence: 99%
“…20 The study results display that the participants of this research are more knowledgeable regarding salt intake compared to other researches for example in a study in Angola medical students revealed that only 6.5% of them are aware of excessive salt intake. 1 A study on cardiovascular risks among university students from developing and developed nations shows significant variation in cardiovascular risk among the young adults studying in universities. 17 Too much salt intake is associated with development of cardiovascular diseases is also in line with other research findings where it has been established that there is association between habitual salt intake and cardiovascular diseases.…”
Section: Discussionmentioning
confidence: 99%
“…High salt consumption can cause high blood pressure and cardiovascular problems. 1 The relationship between dietary salt intake and high blood pressure has been researched by experimental, epidemiological, migration and intervention studies. 2 Hypertension due to high salt intake and their causal relationship is globally accepted.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The knowledge, attitudes and behaviours related to dietary salt intake in highincome countries are low. The same is true for the middle-and low-income countries [41,42]. Consumers are aware of the health outcomes of a high salt intake, but the fundamental knowledge regarding recommended dietary intake, sources in food and the relationship between salt and sodium is lacking.…”
Section: Dietary Salt Reduction Policiesmentioning
confidence: 99%